Effectiveness of Communication Strategies in the Management of COVID-19 Situation in Ghana: The Case of COVID-19 Communication Management within Greater Accra Metropolitan Area - Adjei-Baah, Elvis (UniMAC-GIJ, 2021)
Effectiveness of Communication Strategies in the Management of COVID-19 Situation in Ghana: The Case of COVID-19 Communication Management within Greater Accra Metropolitan Area Communication holds an integral part to government function. To drive the national agenda, government must be seen to be using the best form of communication and the appropriate medium to reach all stakeholders. The failure of government to communicate its policy will result in failure of the entire policy implementation. In times of crisis like the COVID-19 era, leveraging on communication becomes integral for containing, curbing, and preventing the spread of the virus. This study therefore examined the effectiveness of Communication Strategies in the management of COVID-19 Situation in Ghana. To better understand the communication strategies adopted during this pandemic time, the study deploys the quantitative research design. Simple random sampling technique was used to sample 422 respondents for this study. The study further used questionnaire to collect data from the respondents. For analysis, the measures of central tendency such as frequencies, means and percentages were used. The study found that what is communicated by government must be guided by formal processes, engagement of all stakeholders and community leaders in party so that reaching the target audience could be faster. Religious organizations holding strong and entrenched position against the virus would only defeat the considerable efforts made by government to communicate to the masses. Government communication machinery alone cannot win in the fight against COVID-19, deploying all aspect of communication would therefore fast track the communication and reach large proportion of the population. Leveraging on private media houses to communicate government stance on COVID-19 will go a long way to consolidate efforts to reducing the spread and impact of the pandemic. Use of government communication machinery to demystify the negative religious perception on the virus is imperative. Government must design communication that addresses the issues of religiosity when it comes to dealing with COVID-19 pandemic.
Thesis
Keywords: Communication Strategies, Management, COVID-19, Ghana, Communication Management, Greater Accra Metropolitan Area